1976
DOI: 10.1002/ar.1091850403
|View full text |Cite
|
Sign up to set email alerts
|

The postnatal development of the junctional complexes of the mouse Sertoli cells as revealed by freeze‐fracture

Abstract: Mouse testes of newborn to adult were examined by freeze-fracture. Between the newborn Sertoli cells, gap junctions consisting of aggregations of the intramembranous particles (about 8 nm in diameter) are frequently found. Some of the junctions are about 1 mum in diameter and show particle-free regions in the aggregation. Linear arrangements of a few particles, which appear to be the initial formation of the occluding junctions, are seen in the newborn sertoli cells. The occluding junctions are arranged in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(78 citation statements)
references
References 28 publications
6
70
2
Order By: Relevance
“…This example of a claudin shows a transient association with TJs at the time of their formation. TJs form during puberty coincident with a rise in testosterone and expression of the androgen receptor in Sertoli cells (35). To determine whether Cldn3 is expressed during initial TJ formation in pubertal animals, we killed mice at various ages and examined Cldn3 expression.…”
Section: Resultsmentioning
confidence: 99%
“…This example of a claudin shows a transient association with TJs at the time of their formation. TJs form during puberty coincident with a rise in testosterone and expression of the androgen receptor in Sertoli cells (35). To determine whether Cldn3 is expressed during initial TJ formation in pubertal animals, we killed mice at various ages and examined Cldn3 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Gap junctions between neonatal Sertoli cells have also been documented (Nagano and Suzuki, 1976). Change of Cx43 spatial distribution in Sertoli cells from their apical region (3 dpp) to their basal domain (14 dpp) is correlated with the differentiation from a nonpolarized to a polarized epithelium (Vergoween et al, 1991).…”
Section: Bmentioning
confidence: 97%
“…Change of Cx43 spatial distribution in Sertoli cells from their apical region (3 dpp) to their basal domain (14 dpp) is correlated with the differentiation from a nonpolarized to a polarized epithelium (Vergoween et al, 1991). By the end of the second week post partum, the lumen of the tubule is formed (Flickinger, 1967) and gap junctions (Gilula et al, 1976;Nagano and Suzuki, 1976) and tight-junction protein ZO-1 (Byers et al, 1991) distribution changes from the apical to the basal pole of Sertoli cells. More recently, direct interaction (Giepmans and Moolenaar, 1998) and co-localization of the tight junction protein ZO-1 with Cx43 has been documented (Batias et al, 1999).…”
Section: Bmentioning
confidence: 99%
“…In the seminiferous tubules, this is particularly evident between SC and their BTB (Mruk & Cheng 2004, Brehm & Steger 2005, Bergmann 2006, Li et al 2012. Ocln codes for the tight junction protein OCCLUDIN (Furuse et al 1998) and is believed to be the initiator for BTB formation (Nagano & Suzuki 1976), although it is yet detectable in fetal murine SC (Cyr et al 1999). BTB formation due to OCCLUDIN expression begins at around day 10 postpartum and correlates with the initiation of spermatogenesis (Cyr et al 1999, Gerber et al 2014.…”
Section: Sc Btb and Junctional Proteinsmentioning
confidence: 99%
“…It is believed that OCCLUDIN initially forms the BTB at the beginning of spermatogenesis (Nagano & Suzuki 1976) and it was significantly upregulated in the adult KO mice . Gerber et al (2014) demonstrated that pubertal KO mice exhibit a 1 day delay in OCCLUDIN localisation towards the BTB region when compared with their WT littermates (Fig.…”
Section: Sccx43ko Mice and Btbmentioning
confidence: 99%